(untitled) (Acta Scientiarum. Agronomy, 2022)
The forage palm is widely cultivated in semiarid regions. It has a basic chromosome number of x = 11 and polyploids are the main variation. It is propagated via vegetative reproduction, and sexual propagation is rarely used. The objective was to associate the physiological quality of seeds of different cultivars of forage palm with the level of ploidy in the genera Opuntia and Nopalea. The cultivars used were: diploids (2n = 22) ‘F8’, ‘F21’, and ‘IPA Sertânia’; tetraploids (2n = 44) ‘Clone 6 African Elephant Ear’, ‘Mexican Elephant Ear’, and ‘V19’, and octaploids (2n = 88) ‘Round’, ‘Giant’, and ‘IPA Clone 20’. Thousand seed weight, length, diameter, number of seeds per fruit, first count and emergence percentage, shoot and root length, fresh and dry mass, electrical conductivity, and length, width, and fresh and dry weight of cladodes were measured. A nested scheme design was used, with three levels of ploidy and three cultivars within each level. The ploidy level positively influenced the number of seeds per fruit and the physiological quality of the seeds. Cultivars behave differently within the same ploidy level.